2013
DOI: 10.1097/scs.0b013e31828dcd88
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Reduction Malarplasty Utilizing 2 Oblique Osteotomies for Prominent Zygomatic Body and Arch

Abstract: The shape of the zygomatic body and arch have great influences to the facial contour of Orientals. The prominent zygoma makes the appearance look more fierce. Nowadays in China, the number of patients who underwent reduction malarplasty is increasing rapidly. Therefore, it is important to develop a reliable surgical procedure with small wound and good effects. Included in this report were 46 patients with prominent zygomatic body and arch treated between October 2007 and November 2010. Combined intraoral and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Optimal reconstruction of the mobile tongue and mouth floor should aim to maintain the mobility of the remaining tongue by the use of a light, thin, and pliable flap when more than one third of the native tongue is left to preserve as much as possible its important functions including articulation, deglutition, and airway protection. 1 Because the efficacy and effectiveness of the microsurgical reconstruction for head and neck cancer patients have been established, 2-5 continued efforts will target anatomic classification of the defect and functional designing and insetting of the flap. 6-11 We propose here a simplified approach to designing and insetting of the flap for oral and/or oropharyngeal defect reconstruction after partial glossectomy, where the flap design is based on the maximum length and width of the flap, and the surfaces and sulcus are formed during insetting by de-epithelization or safe trimming of the distal part of the flap.…”
Section: Discussionmentioning
confidence: 99%
“…Optimal reconstruction of the mobile tongue and mouth floor should aim to maintain the mobility of the remaining tongue by the use of a light, thin, and pliable flap when more than one third of the native tongue is left to preserve as much as possible its important functions including articulation, deglutition, and airway protection. 1 Because the efficacy and effectiveness of the microsurgical reconstruction for head and neck cancer patients have been established, 2-5 continued efforts will target anatomic classification of the defect and functional designing and insetting of the flap. 6-11 We propose here a simplified approach to designing and insetting of the flap for oral and/or oropharyngeal defect reconstruction after partial glossectomy, where the flap design is based on the maximum length and width of the flap, and the surfaces and sulcus are formed during insetting by de-epithelization or safe trimming of the distal part of the flap.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, complete fracture of the posterior arch has been widely utilized because it can significantly reduce facial width; however, some authors consider post-operative facial depression in the pre-auricular area to be a common problem because the arch is replaced medially and may generate a step-off [ 8 ]. In order to avoid this drawback, many authors advocate an oblique osteotomy of the zygoma arch root [ 29 ]. X-ray images revealed that the bone surrounding the zygomatic arch osteotomy line can be remodeled and partial bone posterior to the articular tubercle of the zygomatic arch is absorbed, which might lead to an depression of the root of the arch and a natural transition of the 2 sides of the osteotomy line, making the midface more slender.…”
Section: Discussionmentioning
confidence: 99%
“…Satoh and Watanabe reported the outcomes of tripod osteotomy and simultaneous fronto-periorbital lifting through a coronal approach in Japanese patients [15] . Cho reported a malarplasty technique by repositioning it medially and superoposteriorly based on either bicoronal or intraoral incision [16] . He favored reduction malarplasty with intraoral and preauricular incision, which had the advantages of a short operative time and simple procedure.…”
Section: Evolution Of Asian Facial Bone Contouring Surgerymentioning
confidence: 99%
“…To extend beyond the limits of intraoral malar reduction, an intraoral infracture technique with incomplete osteotomy has emerged [16,35] . This innovative method involves infracturing the malar bone, thereby reducing the risk of postoperative soft-tissue ptosis and malar reunion.…”
Section: Current Concept Of Asian Malarplastymentioning
confidence: 99%